Can financial literacy and asset ownership affect retirement planning? Insights from the Indonesian family life survey - Novita Kusuma Maharani; Intan Mayang Sari (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: In today's world, financial literacy plays a crucial role in planning for retirement. This study, therefore, investigates the connection between financial knowledge, household asset ownership, and retirement planning.Design/Methodology/Approach: The study considered variables, such as education level, age, gender, marital status, and household location, using data from the Indonesian Family Life Survey (IFLS)-5 at the household level. This study used a sample of 18,627 households spread across 13 provinces in Indonesia to represent the relationship between the variables. The Logit estimation model then examined the impact of financial literacy and household asset ownership on retirement planning.Research findings: The results suggest that individuals with higher financial knowledge are better equipped to plan for their retirement needs. Furthermore, significant asset ownership is also positively linked to retirement planning, as it indicates that an individual is better prepared to face the challenges of old age. Theoretical contribution/Originality: This study contributes to the Life Cycle Hypothesis, which states that individuals will try to keep consumption patterns/needs expenditures and ensure that individual consumption trends remain consistent/constant.Practitioner/Policy implication: This research is expected to be useful as additional information for policy actors, practitioners, and academics in the financial sector to continue actively introducing and disseminating the importance of financial knowledge to the public. Thus, people have alternative and passive income in their old age that does not require working.Research limitation/Implication: The descriptive results found a reasonably large gap between households where there are households with no savings or assets at all. The discrepancy is expected to affect the outcomes of the research.